Revegetation of urban green space rewilds soil microbiotas with implications for human health and urban design. (17th May 2020) - Mills, Jacob G.; Bissett, Andrew; Gellie, Nicholas J. C.; Lowe, Andrew J.; Selway, Caitlin A.; Thomas, Torsten; Weinstein, Philip; Weyrich, Laura S.; Breed, Martin F.
Abstract : Many noncommunicable diseases are linked to degraded diversity in the human and environmental microbiota and are rising globally in epidemic proportions in industrialized urban populations. Reducing this disease burden may be aided by the ecological restoration of microbiota and their habitat in urban green spaces—a process termed microbiome rewilding. Microbiome rewilding could serve as a mechanism to increase urban exposure to biodiversity; biodiversity could introduce microbiota species or functional diversity to improve immune training and regulation in urban populations. As a first step in examining this hypothesis, we explored the microbial diversity and composition of a variety of urban green space vegetation types relative to urban revegetated woodlands of varying levels of vegetation diversity, including lawns, vacant lots, parklands, and remnant woodlands. We generated amplicon sequence variant community profiles from bacterial and archaeal 16S rRNA, fungal ITS1 region, and eukaryotic 18S rRNA marker genes. We also made trophic‐mode predictions of the fungal amplicon sequence variants. Across sites, soil microbiotas in revegetated urban green spaces were similar to remnant woodland microbiotas and differed greatly from lawns and vacant lots. There were several differentially abundant genera likely driving these differences that had strong correlations to plant species richness, soil pH, and conductivity. We provide the first evidence, as far as we know, that revegetation can improve urban soil microbiota diversity toward a more natural, biodiverse state by creating more wild habitat conditions. This evidence supports initiating further studies within the growing field of microbiome rewilding.